UJI DOSIS TRICHOKOMPOS PADA BERBAGAI KOMPOSISI GAMBUT TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L) - Selvia Sutriana; Saripah Ulpah (DINAMIKA PERTANIAN, 2019)
The cultivation of shallots in peat is constrained by the low level of soil fertility and one of methods to increase the nutrient content is by applying trichocompost. Trichokompos is material from plant residues that are composted and mixed with Trichoderma sp. as decomposers. Trichocompost improves soil fertility (soil biology, physics, and chemistry). The purpose of this study was to determine the effect of trichocompost doses on various peat compositions on the yield of shallots. Research was conducted at the Experimental farm of Faculty of Agriculture, Islamic University of , Pekanbaru during 4 months, starting form June to September 2018. The design used was completely randomized factorial with 2 factors, namely Trichocompost Dose, levels 0, 4, 8, 12 g Trichoderma/kg compost and peat composition level: 100, 75, 50, 25%. Parameters tested: plant height, age of tuber formation, number of leaves, number of tubers, and tuber weight. The data were statistically analyzed and the BNJ follow-up test at 5% level. The results showed that the dose of trichocompost combined on peat had a significant effect on all observation parameters and the best treatment was 8-12 g trichoderma/kg compost at 75% peat composition.